Microstructural Evolution and Tensile Properties of Al-Si Piston Alloys during Long-Term Thermal Exposure - Feng Xia; Xiongbo Dong; Jianli Wang; Hongbo Duan; Zhijun Ma; Minxian Liang (Metals, 2024)
The present study investigated microstructural evolution and changes in tensile properties of an Al-Si piston alloy subjected to thermal exposures at 250 and 350 °C for 150, 300, and 500 h. Microstructural and nanoscale precipitates were characterized using a combination of high-angle annular dark field-scanning transmission electron microscopy (HAADF-STEM) images and scanning electron microscopy (SEM). The tensile testing was performed. The results demonstrated that the thermal exposure induced granulation of the δ-Al3CuNi particles, alongside precipitation of the θ-Al2Cu phase particles and AlCu clusters within the matrix. Specifically, an increase in the size and number density of the θ-Al2Cu phase particles was observed with exposure time at 250 °C. Conversely, at 350 °C, the θ-Al2Cu particles exhibited a gradual increase in size with prolonged thermal exposure, coupled with a decrease in their number density. AlCu clusters precipitated solely at a thermal exposure temperature of 350 °C, with precipitation intensifying over time. Moreover, a decrease in the alloy’s tensile strength and an increase in elongation were noted after thermal exposure. Finally, the present study discussed the precipitation mechanisms of θ-Al2Cu particles and AlCu clusters within the grains, suggesting that the AlCu clusters exerted a more effective strengthening effect compared to the θ-Al2Cu particles.